ANALISIS PENGARUH CRUDE OIL PRICE, EARNING PER SHARE, PRICE TO BOOK VALUE, RETURN ON ASSETS DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM PERUSAHAAN BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012–2016 - Apsara, Rama Hadi; Indriani, Astiwi (Faculty of Economics and Business Diponegoro University, 2017)
The aim of this research to analyze the relationship between crude oil price, earning per share, price to book value, return on assets and debt to equity ratio toward stock price. Case study on Coal Mining Company listed in Indonesia Stock Exchange in period 2012-2016. Research population used are Coal Mining Company that listed in Indonesia Stock Exchange (BEI) in period 2012-2016. The sampling technique used in this research is purposive sampling and 14 coal company selected as sample of this research. Analysis used is Multiple Regression Analysis with significance level of 5% that includes classic assumption test, F statistic test, t statistic test and coefficient of determination test (R2). Results from the study showed that earning per share, price to book value and return on assets variables has positive and significant impact to stock price. Then crude oil price ratio and debt to equity ratio has negative and not significant effect to stock price. The result of coefficient of determination test showed the ability of model prediction is 64,7%, while the rest of 35,3% explained by variables outside of this study.